“[...] Será essa prática de leitura e escrita relacionada aos conhecimentos da Bíblia? [...]”: características e contribuições do letramento religioso na Escola Bíblica Dominical - Silva, Antonio Valbert Alves (Universidade do Vale do Rio dos Sinos, 2020)
When assuming literacy as a social practice, it can be said that the practices that are triggered by literacy can be identified and understood in different spaces, including outside the school context. It is with the vision for a reality that is configured in the universe of more than 22 million Brazilians belonging to the evangelical segment in Brazil that, in this research, the objective is to know and understand events and practices of religious literacy experienced by school participants Biblical Sunday (EBD) of the Evangelical Church Assembly of God, also counting on the participation of teachers and family members who participate in Sunday meetings. To achieve this goal, a qualitative-interpretative research was carried out, which used observations in classrooms in the context of EBD, recorded in field notes. There were interviews with three teachers, seven EBD students and mothers of two students, who also made some diary records about their experiences outside the EBD context. In order to proceed with the analysis of the data generated at the different indicated moments, the reflection developed on literacy was based on Heath (1982), Barton (1994), Barton and Hamilton (1998), Street (1984), Soares (2017) and Kleiman (1995). There was also emphasis on the study by Rosowsky (2008), which deals with liturgical literacy, an essential reference for the discussion on religious literacy. From this perspective, literacy, reading and writing events and practices, among other topics developed in the theoretical part, dialogue with the data generated. Among the findings of this work, it was possible to identify religious literacy events promoted from the interactions between adolescents in EBD with their teachers and in family contexts in which reading, writing and orality were present. In addition, EBD, the evangelical church, the family and the regular school show their strength and influence as literacy and religious literacy agencies, in the perception and performance of teachers, EBD students, mothers of adolescents, as they provide experiences reading, writing, orality, also through songs, prayers, sermons, among other literacy events and practices. Given this, it is clear how much religious literacy that was present in the data generated can contribute to the constitution of the social and religious role of its participants in the context of EBD and beyond.
Keywords: Letramento; Letramento religioso; Escola Bíblica Dominical; Igreja evangélica; Lettering; Religious lettering; Dominical Biblical School; Evangelical church; ACCNPQ::Lingüística, Letras e Artes::Lingüística